2014
DOI: 10.1099/vir.0.068544-0
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-activated human α2-macroglobulin interacts with the envelope protein of dengue virus and protects virions from temperature-induced inactivation through multivalent binding

Abstract: Based on the hypothesis that interactions between virions and serum components may influence the outcome of dengue virus (DENV) infections, we decided to use affinity chromatography with domain III from the envelope (E) protein of DENV2 (DIIIE2) as a ligand to isolate virus-binding proteins from human plasma. This approach yielded serum amyloid P (SAP) and a 2 -macroglobulin (a 2 M) as novel viral interactors. After confirming the specific binding of both SAP and a 2 M to DIIIE2 by ELISA, the latter interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Our results show that LRP1 binds DENV virions (Fig 3C) and that this interaction competes, with potency at the nanomolar range, with DENV virion interactions involving other cell surface molecules (Fig 2E). Previous research has already shown that DENV virions can also bind LRP1 ligands [36,65,66], and in the case of α2M, it has been proven that this interaction augments infection [65]. Whether DENV infection may proceed through the formation of a ternary DENV:α2M:LRP1 complex is the subject of ongoing research, but we would like to point out that the pathogenicity of WNV, a flavivirus closely related to DENV, is severely reduced in knockout mice defective for the expression of α2M homologs [67].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our results show that LRP1 binds DENV virions (Fig 3C) and that this interaction competes, with potency at the nanomolar range, with DENV virion interactions involving other cell surface molecules (Fig 2E). Previous research has already shown that DENV virions can also bind LRP1 ligands [36,65,66], and in the case of α2M, it has been proven that this interaction augments infection [65]. Whether DENV infection may proceed through the formation of a ternary DENV:α2M:LRP1 complex is the subject of ongoing research, but we would like to point out that the pathogenicity of WNV, a flavivirus closely related to DENV, is severely reduced in knockout mice defective for the expression of α2M homologs [67].…”
Section: Discussionmentioning
confidence: 99%
“…The procedures for the expression, purification and general characterization of the proteins corresponding to the domain III of the E protein of the four DENV serotypes namely DIIIE1-4, were conducted as previously described. [37]. Receptor-activated α2M was purified from human plasma also following the procedure described elsewhere [37].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations